The influence of direct financial compensation towards future-graduates career choice in hotel industry / Noor Azmi Ahmad ... [et al.] - Ahmad, Noor Azmi; Abdul Aziz, Azri; Kamarudin, Syaquif Yasin; Abdul Aziz, Azdel; Saiful Bakhtiar, Mohd Faeez (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
Hospitality and tourism industry is expanding and becoming one of the major revenue contributors to other nations and Malaysia. It is also one of the largest sectors that employ and provide huge job opportunities for many countries. In fact, influx of workforce is produced by hospitality and tourism schools. Despite the tremendous job opportunities and vacancies in this sector, students from hotel and tourism school rather opt for other job alternatives. This never ending issue could be contributed by many factors including low entry minimal wages. Therefore, this study examines direct financial compensation influencing career choice in hotel industry among the students. Through self reported questionnaire, 265 respondents were approached using proportionate stratified random sampling method. The study shows a direct relationship on factor in research which is direct financial compensation and career choice intention in the hotel industry. Main focus on graduate is the satisfactory introductory level salary as the pull factor to join the industry beside interest and career advancement.